Tool to Support Citizen Participation and Multidisciplinarity in Food Innovation: Circular Food Design - Sijtsema, Siet J.; Fogliano, Vincenzo; Hageman, Madelinde (Frontiers in Sustainable Food Systems, 2020)
Innovations are urgently required to transform towards a more circular food system in which the food production and processing is more sustainable and the dietary patterns of consumers are more healthy and sustainable. It is needed to be more innovative in a multidisciplinary and consumer oriented way. Therefore this paper introduces circular food design model and presents some applications. This paper presents background information regarding relevant models of product development and combines approaches and insights from different disciplines, such as consumer and food science, all present in the food system. In addition, the linkage with design thinking is addressed. Moreover research questions are presented focused on the identification, development and optimization phase with regard to agricultural production, food storage, processing, retail and consumption. This circular food design model can support a way of thinking that will lead to multidisciplinary and citizen participating in food product development. The added value of circular food design model is; first, the model stimulates a citizen participation approach in a creative way; second, the model supports communication and collaboration among all involved disciplines. The newly developed circular food design model visualizes an iterative approach meant to be a flexible and creative tool to structure the new food development in the different phases to support value creation in the food system in order to support its transition.